The Fracture Ankle Implant Review (FAIR) study: a national multicentre retrospective review of practice in implant choice, fixation methods, and outcomes in fixation of the fibula in ankle fractures - William G. Fishley; Thomas Baldock; Alan J. Hilley; Rory Morrison; Paul Baker; Dave Townshend; FAIR Study Collaborating Authors (Bone & Joint Open, 2025)
Aims: In fixation of the fibula in ankle fractures, the AO Foundation advocates using a lag screw and one-third tubular neutralization plate for simple patterns. Where a lag screw cannot be placed, bridging fixation is required. A local pilot service evaluation previously identified variance in use of locking plates in all patterns with significant cost implications. The Fracture Ankle Implant Review (FAIR) study aimed to evaluate current practice and implant use across the UK, and review outcomes and complication rates between different fibula fixation methods. Methods: The study was supported by CORNET, the North East orthopaedic trainee research collaborative, and the British Orthopaedic Trainee Association (BOTA). Data were collected using REDCap software from 22 centres in the UK retrospectively for a one-year period between 1 January 2019 and 31 December 2019 on injury mechanism, fracture characteristics, comorbidities, fixation, and complications. Follow-up data were collected to at least two years from surgery. Results: A total of 1,471 ankle fractures which involved fixation of the fibula were analyzed; a one-third tubular plate was used in 883 cases (59.7%), a locking plate in 470 cases (31.8%), and other methods in 118 cases (8.1%). There was significant difference between centres (p < 0.001) in terms of the implant type which was used. Other factors associated with implant type were age, diabetes, osteoporosis, open fractures, and comminuted fractures. Incidence of lateral wound breakdown and infection was higher in locking plates than one-third tubular plates (Lateral wound breakdown p = 0.008, Infection p = 0.039) in AO44B fractures. There was no significant difference in nonunion, fixation failure, or removal of metalware. Conclusion: There is significant variation in practice in the UK in implant use for fixation of the fibula in ankle fractures. If a locking plate is used unnecessarily, where a one-third tubular shows equivalent outcomes, this incurs additional cost and may increase the risk of lateral wound complications. We would encourage surgeons with high locking plate usage to evaluate their own unit’s practice against these data. Cite this article: Bone Jt Open 2025;6(7):841–849.